STAFF MOBILITY ROLE IN THE INSTITUTION’S INTERNATIONALISATION PROCESS - Jolanta Preidienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2016)
The aim of article is to overview existing research made in the field of international staff mobility and its impacts on institution’s internationalisation process. Internationalization of higher education is an integral part of higher education institutions’ activities. One of the key activities in the higher education institution’s internationalization process is its students and staff mobility. Mobility achievements are considered as one of the key criteria during evaluation and accreditation of higher education institutions. Thus a deeper analysis of the current research made in the field is necessary in order to make quantitative and qualitative impact on the higher education institutions’ internationalisation process.